'Ultra-left' anarchists and anti-fascism in the Second Republic. (1st September 2016) - Evans, Danny
This article investigates the anarchist understanding of fascism during the Second Republic, and particularly during the abstention campaign of 1933, when the practice of radicals in the National Confederation of Labour (CNT) has been described as 'ultra-left' in view of its sectarianism and insistence on the need for an insurrectionary response to the threat of the right. The article explores the comparison made to the German Communist Party (KPD) during the so-called 'Third Period', and the lessons that anarchists in Spain attempted to draw from the rise of Hitler.